Time-lapse imagery of peruvian boobies sula variegata reveals nest abandonment caused by tick hyperinfestation - Burga-Domínguez C. (2020)
Severe tick infestation in seabird colonies causes discomfort in reproductive adults, offspring mortality, and nest abandonment. This study used time-lapse cameras to examine the relationship between Ornithodoros amblus tick infestation and Peruvian Booby Sula variegata nest abandonment in four locations along the Peruvian coast between August 2016 and November 2018. The percent occurrence of discomfort in nesting birds (preening and standing on the nest) recorded by the cameras was used as an indicator of tick infestation. The tick density insideand outside the abandoned colonies was also evaluated. In five of the six colonies, complete nest abandonment occurred over an interval of two to three weeks. The percent occurrence of discomfort behavior was exponentially related to the percentage of nest abandonment, indicating that reproductive failure was related to tick hyperinfestation. This conclusion was reinforced by the fact that in a colony where no discomfort behaviors were recorded, there was no nest abandonment (53% of successful nests, n = 17). The tick density was higher inside(mean ± SD: 105.41 ± 92.8 ticks/500 mL of guano) than outside (43.08 ± 39.8 ticks/500 mL of guano) of the recently abandoned colonies, confirming that nest desertion was caused by tick hyperinfestation. The results of this study reveal that the use of time-lapse cameras in booby colonies is feasible not only for the determination of reproductive success but also for the identification of causes of nest abandonment.